Makna Leksikal dan Kontekstual Budidaya Pertanian Jagung di Desa Kalibareng Kendal: Kajian Semantik - Afifah Indriastuti; Eka Yuli Astuti; Widodo Widodo (CV. ALIM'SPUBLISHING, 2026)
Abstract.. The development of modernization in corn farming in Kalibareng Village, Patean District, Kendal Regency has the potential to cause the loss of traditional terms used by the farming community. This study aims to describe and analyze the lexicon of corn farming in Kalibareng Village, Patean District, Kendal Regency, and to reveal the lexical and contextual meaning contained therein. This study uses a descriptive qualitative approach with field research and semantic studies as the main approach. Data were obtained through participatory observation, in-depth interviews, and documentation of corn farmers in Kalibareng Village. The results show that there are 44 lexicons divided into three categories, namely cultivation processes, agricultural tools, and agricultural materials. The lexical meaning in the lexicon refers to the basic meaning according to its referent, while the contextual meaning is influenced by the situation of use in agricultural activities. The contextual meanings found include process context, time context, and function context. This study shows that the corn farming lexicon not only functions as a communication tool, but also represents local knowledge, culture, and farming experiences of the Kalibareng Village community that have been passed down from generation to generation.